The role of institutionalized cooperation in transboundary basins in mitigating conflict potential over hydropower dams - Schmeier, Susanne (Frontiers in Climate, 2024)
Numerous dams are currently being built, many of them in transboundary basins. This can lead to disagreements and conflicts between riparian states, compromising not only environmental and social sustainability, but also regional stability and peace. Addressing such conflict risks, states have developed legal and governance mechanisms to address the conflict potential around dams, ranging from international water law principles to dam-specific provisions in basin treaties and from basin management plans to environmental impact assessment approaches. This paper assesses whether, how and to what extent such institutionalized governance mechanisms can prevent or mitigate conflict through both a global perspective (based on global datasets on international water treaties and basin organizations) and a case study perspective (conducting an in-depth analysis of three basins the Mekong, Zambezi, and Senegal river basins). It finds that globally there is a shortcoming in institutionalized cooperation mechanisms preventing and mitigating conflict risks over dams, but in those albeit rather few basins where they do exist, they can reduce conflict risks and thus benefit riparian people, ecosystems, and countries. These findings contribute to the broader discourse on the role of international water law and basin organizations in sustainably managing shared water resources and support calls for the strengthening of those.